Kengo Kuma : complete works - Frampton, Kenneth, 1930- (London : Thames & Hudson, 2012)
The quintessential Japanese architect of today, Kengo Kuma has forged a modern design language that artfully combines the countrys traditional building crafts with sophisticated technologies and materials. Associating a deep understanding and respect for native construction techniques with a more globalized outlook than many of his compatriots, Kengo Kumas work represents a significant generational shift in a country rich with contemporary architecture. From his iconic Glass House (1995) to the Nezu Museum in Tokyo, this is the complete record of Kengo Kumas built work, comprising twentyfour projects to date. Architecture historian Kenneth Frampton frames Kumas work in the context of post-war Japans flourishing architecture scene and influential figures and offers a perspective on the international acclaim of Kumas ideas and buildings. Projects are organized by the material themes that have come to define the architects output: Water and Foliage
Keywords: Kuma, Kengo, -- 1954-.; Architecture -- History -- 20th century -- Japan; Architecture -- History -- 21st century -- Japan